Is the Jarman underprivileged area score valid?. Issue 6483 (8th June 1985) - Charlton, J R; Lakhani, A
Abstract : A recently published validation of an underprivileged area score, which is intended to reflect factors that increase general practice workload or pressure on their services, was incomplete; a validation based on criteria other than the opinion of general practitioners is also required. Areas with higher mortality from diseases where general practitioner intervention can reduce mortality substantially are likely to have a greater need for general practice services. Similarly, the need for general practitioner services should be higher where the incidence of such treatable conditions is higher. This paper describes the association between Jarman's score and (a) mortality from causes that are amenable to general practice intervention and (b) incidence of two diseases where general practice intervention is important. Using these data the score appears to have external criterion validity and thus is likely to reflect, at least crudely, the need for general practitioner services.